Time period effects of changes in interest rates on stock-prices in Singapore. - Tan, Hock Yew. (2009)
Although there has been much speculations on how changes in interest rates can affect stock prices in the Singapore stock market, the amount of research in this arena is limited. One of the objectives of this research is to establish a relationship between the rate of change of stock prices and the rate of change of interest rates in Singapore. More importantly, the research is also carried out to ascertain at what time period stock prices in Singapore react to a change in interest rates. Representing one of the first local studies, the research covered both the overall stock prices as well as certain segments of stock prices in the Singapore stock market, namely, the industrial segment, the finance / banking segment, the hotel segment and the properly segment.